Guest

f(x+y+z) =f(x).f(y).f(z) for all x , y , z and f(2)=4 , f(0) =3 then f(2) = ans is 12 plzz explain..

f(x+y+z) =f(x).f(y).f(z) for all x , y , z and f(2)=4 , f(0) =3 then f(2) = 


ans is 12


plzz explain..

Grade:11

2 Answers

dileep munugoti
16 Points
10 years ago

i think the question is wrong as keep x=0 and y=0 then f(z)=f(0).f(0).f(z) then f(0) should be equal to 1 or -1 but it was given f(0)=3

Ranjita yadav
35 Points
10 years ago

ques. is crect , actually it is  f ''(0) =3

Think You Can Provide A Better Answer ?